Division of Inheritance Assets in a Serial Polygynous Marriage Based on Islamic Law - Athifatul Wafirah (Fakultas Hukum Universitas Airlangga, 2024)
Marriage law in Indonesia adheres to the principle of non-absolute monogamy. The Marriage Law states that a husband may have more than one wife if the parties concerned wish, or this is known as polygamy. Polygamy is divided into two, namely polygyny and polyandry, but only polygyny is recognized in Indonesia. Polygyny has been regulated in such a way by the Government, however, the practice of serial polygyny (underhand) is still widespread, which has an impact on the distribution of assets. This research aims to find out about the validity of siri polygynous wives as heirs and the judge's decision ratio regarding the distribution of assets to siri polygynous wives. The research model used is normative juridical with a statutory approach, conceptual approach and case approach. So the result is that the wife of a polygynous marriage in a serial manner gets a division of assets (both joint assets and inherited assets) if the marriage is solemnized and in court can prove that the marriage actually occurred and was in accordance with the requirements and pillars of Islamic law.